Flatus Incontinence and Fecal Incontinence: A Case-Control Study. Issue 4 (24th March 2022) - Trieu, Rose Q.; Mazor, Yoav; Prott, Gillian; Jones, Michael P.; Kellow, John E.; Schnitzler, Margaret; Malcolm, Allison
Abstract : BACKGROUND: Incontinence to gas can be a troublesome symptom impacting quality of life for patients even in the absence of fecal incontinence. Whether isolated flatus incontinence represents part of the spectrum of true fecal incontinence or a separate condition with a different pathophysiology remains unclear. OBJECTIVE: This study aimed to evaluate the clinical features and anorectal physiology in women presenting with severe isolated flatus incontinence compared to women with fecal incontinence and healthy asymptomatic women. DESIGN: This was a retrospective case-control study of prospectively collected data. SETTINGS: Data from participants were obtained from a single tertiary Neurogastroenterology Unit in Sydney, Australia. PATIENTS: Data from 34 patients with severe isolated flatus incontinence, 127 women with fecal incontinence‚ and 44 healthy women were analyzed. MAIN OUTCOME MEASURES: The primary outcomes were clinical (including demographic, obstetric, and symptom variables) and physiological differences across the 3 groups. RESULTS: Patients with flatus incontinence were significantly younger (mean 39 versus 63 years; p = 0.0001), had a shorter history of experiencing their symptoms ( p = 0.0001), and had harder stool form than patients with fecal incontinence ( p = 0.02). Those with flatus incontinence had an adverse obstetric history and impaired anorectal physiology (motor and sensory, specifically rectal hypersensitivity) but to a lesser extent than patients with fecal incontinence. LIMITATIONS: This study was limited by its retrospective design and modest sample size. CONCLUSIONS: Anorectal physiology was impaired in patients with flatus incontinence compared to healthy controls, but to a lesser extent than in those with fecal incontinence, raising the possibility that flatus incontinence could be a precursor to fecal incontinence. As clinical and physiological findings are different from healthy controls (including the presence of visceral hypersensitivity), isolated flatus incontinence should be considered a distinct clinical entity (like other functional GI disorders), or possibly part of an incontinence spectrum rather than purely a normal phenomenon. See Video Abstract at http://links.lww.com/DCR/B946 . INCONTINENCIA DE FLATOS E INCONTINENCIA FECAL: UN ESTUDIO DE CASOS Y CONTROLES: ANTECEDENTES: La incontinencia de gases puede ser un síntoma molesto que afecta la calidad de vida de los pacientes incluso en ausencia de incontinencia fecal. Aún no está claro si la incontinencia de flatos aislada representa parte del espectro de la incontinencia fecal verdadera o una condición separada con una fisiopatología poco clara. OBJETIVO: Evaluar las características clínicas y la fisiología anorrectal en mujeres que presentan incontinencia grave aislada de flatos, en comparación con la incontinencia fecal y mujeres sanas asintomáticas. DISEÑO: Este fue un estudio retrospectivo de casos y controles de datos recolectados prospectivamente. AJUSTE: Los datos de los participantes se obtuvieron de una sola Unidad de Neurogastroenterología terciaria en Sydney, Australia. PACIENTES: Se analizaron los datos de 34 pacientes con incontinencia grave aislada de flatos, junto con 127 mujeres con incontinencia fecal y 44 mujeres sanas. PRINCIPALES MEDIDAS DE RESULTADO: Los resultados primarios fueron clínicos (incluidas las variables demográficas, obstétricas y de síntomas), así como las diferencias fisiológicas entre los tres grupos. RESULTADOS: Los pacientes con incontinencia de flatos eran significativamente más jóvenes (media de 39 años frente a 63 años, p = 0, 0001), tenían un historial más corto de experimentar sus síntomas (p = 0, 0001) y tenían heces más duras que los pacientes con incontinencia fecal (p = 0, 02). Aquellos con incontinencia de flatos tenían antecedentes obstétricos adversos y fisiología anorrectal alterada (motora y sensorial, específicamente hipersensibilidad rectal); aunque en menor medida que las pacientes con incontinencia fecal. LIMITACIONES: Este estudio estuvo limitado por su diseño retrospectivo y tamaño de muestra modesto. CONCLUSIONES: La fisiología anorrectal se vio afectada en las pacientes con incontinencia de flatos en comparación con las controles sanos, pero en menor medida que en aquellas con incontinencia fecal, lo que plantea la posibilidad de que la incontinencia de flatos pueda ser un precursor de la incontinencia fecal. Dado que los hallazgos clínicos y fisiológicos son diferentes a los de los controles sanos (incluida la presencia de hipersensibilidad visceral), la incontinencia de flatos aislada debe considerarse como una entidad clínica distinta (al igual que otros trastornos gastrointestinales funcionales), o posiblemente como parte de un espectro de incontinencia en lugar de un trastorno puramente a un fenómeno normal. Consulte Video Resumen en http://links.lww.com/DCR/B946 . (Traducción—Dr Yolanda Colorado )